From Flour to Figures: visualizing job costing in the bakery industry - San, Suzana; Nik Wan, Nik Zam; Razak, Syuhaila; Abdullah @ Abd Aziz, Azilawati; Saidi, Noraida (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Job Costing is perceived as a difficult topic for non-accounting students to understand, as it requires thorough calculations and numerical data. An infographic illustration was designed to present the Job Costing process in a simple and more visual way to address the issue. The bakery industry was selected to provide relatable real business and visually engaging materials to further enhance students’ comprehension of the concepts. The infographic breaks down the cost elements of Job Costing, making it easier for students to grasp the concepts and facilitate the cost calculation. An interactive quiz was created to foster fun and engaging classroom experiences for both students and lecturers. The novelty of these interactive tools is the ability to transform traditional teaching approaches into visual and engaging experiences, thereby improving students’ performance and lecturers’ teaching methods. The use of familiar industry also increases students’ relatability and comprehension of this concept. Furthermore, the adaptability of this innovation to e-learning platforms, educational content, and teaching materials offers potential commercial applications. In conclusion, the integration of infographics and interactive quizzes developed effective teaching methods for Job Costing. Consequently, these interactive tools transformed the difficult topic into an enjoyable and engaging learning experience for non-accounting students.